2017
DOI: 10.18632/oncotarget.16359
|View full text |Cite
|
Sign up to set email alerts
|

The associations of genetic polymorphisms inCYP1A2andCYP3A4with clinical outcomes of breast cancer patients in northern China

Abstract: BackgroundCytochrome P450 (CYP) 1A2 and CYP3A4 may play a role in the differentiation of clinical outcomes among breast cancer women. This study aimed to analyze the association of genetic polymorphisms in the CYP1A2 and CYP3A4 genes with clinicopathological features, protein expression and prognosis of breast cancer in the northern Chinese population.ResultsFirstly, SNP rs11636419, rs17861162 and rs2470890 in the CYP1A2 were significantly associated with age and menstruation status. And SNP rs11636419 and rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…On the other hand, we cannot confirm the previously reported association between this SNP and the age of onset of mammary tumours, which may be related to differences in the cohort populations and to the small representativeness of this SNP, accounting for only 23.7% of the animals included in the present study. OS of breast cancer 33,34. Data from the present investigation identified COMT haplotypes with apparently opposite effects regarding CMTs progression, reinforcing the role of hormonal factors as prognosticators in this type of neoplasm.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…On the other hand, we cannot confirm the previously reported association between this SNP and the age of onset of mammary tumours, which may be related to differences in the cohort populations and to the small representativeness of this SNP, accounting for only 23.7% of the animals included in the present study. OS of breast cancer 33,34. Data from the present investigation identified COMT haplotypes with apparently opposite effects regarding CMTs progression, reinforcing the role of hormonal factors as prognosticators in this type of neoplasm.…”
supporting
confidence: 71%
“…Our results emphasize the importance of genetic variation in estrogens metabolic pathways as prognosticators in both human and canine mammary neoplasia. Recently, some investigators described an association between genetic SNP in Cytochrome P450 (CYP) enzymes (involved in estrogens biosynthesis) and the patients' age, tumour size, histological grade and OS of breast cancer . Data from the present investigation identified COMT haplotypes with apparently opposite effects regarding CMTs progression, reinforcing the role of hormonal factors as prognosticators in this type of neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…A GWAS study in Chinese Han illustrated that rs3751599 is a human height-related SNP in CYP19A1 locus [ 25 ]. CYP1A2 rs2470890 polymorphisms have been studied in breast cancer of northern China, and in depression of Chinese Han, as well as in pharmacogenomics analysis among Chinese [ 26 28 ]. However, neither of these two SNPs were investigated in T2DM, and this is the first study to carry out the data-based association analysis and found their protective effects on T2DM in certain populations.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, we investigated whether these SNPs had any impact on cinacalcet response in healthy Chinese subjects after receiving a single dose under fasting conditions. We selected SNPs of CYP3A4, CYP2D6, and CYP1A2 enzymes, which are commonly reported to affect the metabolism of other drugs, to explore whether they have any effect on the PK of cinacalcet under fasting conditions (28)(29)(30)(31)(32). We present the following article in accordance with the CONSORT reporting checklist (available at http://dx.doi.org/10.21037/atm-20-1329).…”
Section: Introductionmentioning
confidence: 99%